2021
DOI: 10.1016/j.jbc.2021.100994
|View full text |Cite
|
Sign up to set email alerts
|

CDC5L promotes early chondrocyte differentiation and proliferation by modulating pre-mRNA splicing of SOX9, COL2A1, and WEE1

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Aggrecan, a cartilage-specific proteoglycan core protein, also plays a key role in articular cartilage and joint function [41]. In the process of chondrocyte differentiation, COL2A1 was expressed significantly in the early stage of the differentiation process, while ACAN was expressed at the late stage, indicating a cartilage maturation [42,43]. According to the current results, COL2A1 is upregulated, but ACAN expression is suppressed on the GlyCVD-BCC surface.…”
Section: Gene Expression Of Hbmscs On the Hybrid Nanostructuressupporting
confidence: 55%
See 2 more Smart Citations
“…Aggrecan, a cartilage-specific proteoglycan core protein, also plays a key role in articular cartilage and joint function [41]. In the process of chondrocyte differentiation, COL2A1 was expressed significantly in the early stage of the differentiation process, while ACAN was expressed at the late stage, indicating a cartilage maturation [42,43]. According to the current results, COL2A1 is upregulated, but ACAN expression is suppressed on the GlyCVD-BCC surface.…”
Section: Gene Expression Of Hbmscs On the Hybrid Nanostructuressupporting
confidence: 55%
“…COL2A1 is a crucial gene expressed in the early stage of chondrocyte differentiation of MSCs, which in turn generates type II collagen, the main protein of the cartilage ECM [42]. Type II collagen plays a critical role in articular cartilage due to its elasticity in joint function [41].…”
Section: Gene Expression Of Hbmscs On the Hybrid Nanostructuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies had reported the role of CDC5L in bone development. CDC5L was expressed in chondrocytes proliferating from mouse embryonic bone growth plates, and CDC5L mediates the promotion or inhibition of pre-mRNA splicing of early cartilage genes (Sox9 and Col2a1) or Wee1, respectively (Jokoji et al, 2021). CUL1 and CXCL10 were also frequently reported in immune regulation (Sorrentino et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…When the cell confluence reached 80%, the cells were passaged at a ratio of 1:3. According to literature, cells derived from OPLL mainly consist of fibroblasts, osteoblasts, and chondrocytes [ 39 , 40 ]. In this article, we define these cells as OPLL cells.…”
Section: Methodsmentioning
confidence: 99%